Constitutionalization of tax definition - Ruiz de Castilla Ponce de León, Francisco J. (2013)
The author works with the increasing constitutionalization process of Tax Law in the country as starting point; then, makes an analysis of tax concept evolution from a general tax law theory point of view. Afterwards, explains Tax Law Constitutionalization specifying main communicating vessels between Constitutional and Tax Law. Finally, highlights the most important values and goals related with taxing and constitutional control implementation by the Tax Court.